Historic Lynching and Corporal Punishment in Contemporary Southern Schools. (18th November 2019) - Ward, Geoff; Petersen, Nick; Kupchik, Aaron; Pratt, James
Abstract: This study examines how corporal punishment in contemporary public schools, a disciplinary practice concentrated in southeastern U.S. states, relates to histories of lynching in the region. Using school-level data from the U.S. Department of Education, we examine these relationships in a series of multi-level regression models. After controlling for numerous school- and county-level factors, we find an increased likelihood of corporal punishment for all students in counties where greater numbers of lynchings occurred, and that lynching is particularly predictive of corporal punishment for black students. Consistent with prior research associating historic lynching with contemporary violence, these results suggest general and race-specific legacies for violent school discipline. We consider potential mechanisms linking histories of lynching with school corporal punishment, and implications for research and policy.